The Correlation between Students’ Performance in Integrated Exercises and Their Academic Achievements in English Course for Non-English Department - Qorinta Shinta (Universitas Dian Nuswantoro, 2020)
Abstract. The English Course in Public Health Faculty of Diponegoro University is expected to develop the reading skills of the students through various exercises. However, its main goal is to help students identify simple, complex and compound sentences and how to organize them into good paragraphs. As in the Faculty of Public Health, the English Course is only given once in the first Semester, the exercises in each of the lesson is very compact which consists of Reading Text, Comprehension Questions, Word Study, Grammar and Usage, and Writing, in short these are called integrated exercised. Some students did very well on the exercises while others did not. The purpose of the study is to examine the relationship between the students’ performance in integrated exercises and their academic achievements of Diponegoro University Students majoring in Public Health who took English Course. The academic achievements in this study refer to their Mid-Term test Scores. Method of the Study: in the study of Diponegoro University Freshmen majoring in Public Health, a descriptive qualitative method was used to determine whether or not there is a correlation between reading and writing exercises and their academic achievements. The instruments used are the scores of 3 taken from exercises in unit 1, 2 and 3 and 1 Mid-Term test. The population of this research is 73 Public Health students of Diponegoro University taking English 1 Course. The data analysis result shows that Sig score is 0,000 < 0,05 therefore Ho is declined and Ha is accepted, which means there is a correlation between reading and writing practices scores and mid test scores 0.403 which is positive. Therefore, it can be concluded that the higher their writing scores are, the higher mid test scores will be.Key words: correlation, English course, integrated exercises, mid-term testAbstrak. Mata kuliah Bahasa Inggris di Fakultas Kesehatan Masyarakat diharapkan mampu mengembangkan ketrampilan membaca mahasiswa memalui berbagai Latihan soal-soal. Namun, tujuan utama dari mata kuliah ini adalah membantu para mahasiswa menindentifikasi kalimat – kalimat sederhana, kompleks dan majemuk serta bagaimana membentuk kalimat – kalimat tersebut dalam bentuk paragraph. Karena mata kuliah Bahasa Inggris hanya disajikan satu kali, maka latihan-latihan soal pada setiap unit dibuat sangat padat yang terdiri dari Teks Bacaan, Pertanyaan tentang bacaan, Kosakata, Grammar dan fungsinya, serta Latihan writing. Ada mahasiswa yang bisa mengerjakan Latihan soal dengan sangat baik tetapi ada juga yang kesulitan. Tujuan dari peneltian ini adalah untuk melihat korelasi antara Nilai dari Latihan soal reading dan writing serta prestasi akademik dari Mahasiwa baru Universitas Diponegoro jurusan Kesehatan Masyarakat. Prestasi akademik dalam hal ini adalah nilai Mid-term test mereka. Dalam penelitian pada mahasiswa baru Universitas Diponegoro jurusan Kesehatan Masyarakat, digunakan metode deskriptif kualitatif untuk menetukan apakah ada atau tidak ada korelasi antara Latihan soal reading dan writing dengan prestasi akademik mereka. Instrumen yang digunakan pada penelitian ini adalah 3 nilai yang diambil dari 3 latihan soal Unit 1, 2 dan 3. Jumlah populasi adalah 73 Mahasiswa Kesehatan Masyarakat Universitas Diponegoro yang mengambil mata kuliah Bahasa Inggris 1. Hasil dari data analisis menunjukkan bahwa nilai Sig 0,000 < 0,05 sehingga Ho ditolak dan Ha diterima, yang berarti ada korelasi antara nilai Latihan writing dengan nilai ujian tengah semester 0.403 positif. Sehingga bisa disimpulkan bahwa semakin tinggi nilai mereka pada Latihan writing akan semakin tinggi juga nilai mereka dalam Ujian Tengah Semester.Kata kunci: korelasi, mata kuliah bahasa Inggris, nilai latihan soal terpadu, nilai Ujian Tengah Semester